2013
DOI: 10.1002/mgg3.14
|View full text |Cite
|
Sign up to set email alerts
|

The +3187A/G HLA‐G polymorphic site is associated with polar forms and reactive reaction in leprosy

Abstract: Considering that variability in immune response genes has been associated with susceptibility to leprosy and with disease severity, leprosy presents clinicopathological variants that are highly associated with the immune response, HLA-G has a well-recognized role in the modulation of the immune response, and polymorphisms at the 3′ untranslated region (UTR) of the HLA-G gene may influence HLA-G production, we studied the polymorphic sites at the 3′ UTR of the HLA-G gene in leprosy and their association with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(71 reference statements)
2
7
0
Order By: Relevance
“…A perfect LD (D′ = 1; r 2 = 1) was observed between the SNP +3010C/G and +3142G/C ( P < 0.001) in control and BPH groups, and also between 14 bp Ins/Del and +3027A/C ( P < 0.001) in PCa group (data not shown). LD was not observed among the SNP +3003 T/C and +3027A/C (in control and BPH groups) or +3035C/T (in control group), corroborating data for these polymorphic sites in others studies . Altogether, our results suggest a strong LD between HLA‐G 3′UTR polymorphic sites.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A perfect LD (D′ = 1; r 2 = 1) was observed between the SNP +3010C/G and +3142G/C ( P < 0.001) in control and BPH groups, and also between 14 bp Ins/Del and +3027A/C ( P < 0.001) in PCa group (data not shown). LD was not observed among the SNP +3003 T/C and +3027A/C (in control and BPH groups) or +3035C/T (in control group), corroborating data for these polymorphic sites in others studies . Altogether, our results suggest a strong LD between HLA‐G 3′UTR polymorphic sites.…”
Section: Resultssupporting
confidence: 91%
“…As the 3′UTR is a regulatory region encompassing genetic variants that influence HLA‐G mRNA availability and stability as well as determine differential binding of specific microRNAs, it is very important to evaluate such variants in patients with prostate tumors . In the Southern Brazilian population assessed in this study, strong LD between HLA‐G 3′UTR polymorphic sites was observed, corroborating previous data . Seven haplotypes here identified (UTR‐1 to ‐7) among the three studied groups (control, BPH and PCa) correspond to frequent haplotypes previously described to worldwide populations .…”
Section: Discussionsupporting
confidence: 88%
“…Leprosy-associated class II HLA genes include HLA-DQA1 in Brazilians (123), HLA-DQB1 * 06 and HLA-DQB1 * 07 in Mestizo populations (121), HLA-DRB1 * 11 in Brazilians (124), HLA-DRB1 * 1501 in Chinese and Indians (125,126), and HLA-DRB1 * 1501 in Indians (125,126). In addition, other antigen-processing and presentation-related genes were found to be associated with leprosy, such as the MICA gene (127), MICB gene (127), HLA-G gene (128), and TAP1 gene (129). Interestingly, even in the same population, some HLA genes showed susceptibility to leprosy and others showed resistance to leprosy, which indicated that some HLA molecules could activate T cells by presenting M. leprae antigens, while others are responsible for the T cell anergy in leprosy (121).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 99%
“…Other associations have only been found once, and the implication of the tested genes in leprosy pathogenesis must be considered with caution: IFNγ and HLA-G in Brazil [ 63 , 64 ]; TLR4 and leukotriene A4 hydrolase ( LTA4H ) in Ethiopia [ 65 , 66 ]; vitamin D receptor ( VDR) [ 67 , 68 ], killer cell immunoglobulin like receptor, two Ig domains and short cytoplasmic tail 3 ( KIR2DS3 ) [ 69 ], heat shock protein 1A ( HSPA1A ), and IL-23R in India [ 70 , 71 ]; lymphotoxin-α ( LTA ) in Malawi [ 53 ]; complement fraction 4 ( C4A ) in Thailand [ 72 ]; IL-12B in Mexico [ 73 ]; IL-12RB2 in Japan [ 74 ]; natural resistance-associated macrophage protein 1 ( NRAMP1 ) in Mali [ 75 ]; laminin 2 ( LAMA2 ) in Indonesia [ 76 ]; defensin-β1 ( DEFB1 ) in Mexico [ 77 ]; and optic atrophy 1 ( OPA1 ) in China [ 78 ]. Interestingly, for VDR, one study identified a polymorphism associated with leprosy when comparing MB to PB [ 67 ], while a second study identified a haplotype when comparing MB to controls and another haplotype when comparing PB to controls [ 68 ].…”
Section: Human Genetics Of Leprosy Subtypesmentioning
confidence: 99%